- Al- Imam Al- Nawawy's approach for Avoidance of Contradictions between Hadiths through His Sahih Muslim Interpretation- Applied Study on trading and sharecropping chapters - Ahmtay, Arban Ghani (Arab Journal for Sciences and Research Publishing, 2018)
This Study aims at revealing practical lessons taken from the research papers on disagreements and giving of preference in the science of Fundamentals of Islamic Jurisprudence by collecting seemingly contradict narrations، in the explanation of Sahih Muslim، from the beginning of book of the Transactions to the end of book of the Sharecropping and presenting the methods that Imam An- Nawawi had in avoiding contradictions.What motivated us to conduct this study was the lack of practical examples on contradictory and giving preference hadiths in the books of Fundamentals of Islamic Jurisprudence science. Ever thought there are many these kinds of books in the science of Islamic Jurisprudence and in the explanations of the books of hadiths but these hadiths are spread everywhere and they need to be collected and to be studied accordingly. The explanation of Sahih Muslim is the book in which these hadiths are found that are seemingly contradictory. Moreover، there you can find the methods that the scholars followed to avoid contradictions between such hadiths. And lastly the study of the methods of the scholars that they followed in avoiding contradictions between seemingly contradictory hadiths are the maters that help the Faqih to avoid disagreement and confusion between different opinions and different conclusions on particular religious rulings.
Keywords: Collection; preference; contradiction; hadiths; Al-Nawawi; explanation of Sahih Muslim; sales; irrigation